2020
DOI: 10.37185/lns.1.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Events Involved in Puberty: A Revisit to Existing Knowledge

Abstract: Puberty is a multifaceted complex phenomenon, comprised of a series of events, controlled by hormones and other regulatory factors. It is the transition period between childhood and adolescence with key important changes occurring in physical, biological, cognitive, psychological and social spheres of an individual’s life. These changes are not only important in the personal life of an individual but also affect his/her relationship with others in the society. The interaction between the hypothalamus and anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The aim of the present study was to verify the relationship between hormonal markers and biological maturation markers in the neuromotor abilities of female children. Similar to the objective of the present study, Lowe et al, [37] addressed that hormonal markers in the group of estrogens including estradiol interact with strength levels in women throughout life, and Aslam et al, [8] recently reported that there is a relationship between hormone levels during puberty and neuromotor skills in subjects of both sexes. In the same context to the objective of the present study, seeking to find relationships between maturation and neuromotor performance, Volver et al, [27], in a longitudinal study, analyzed 34 female subjects aged between 11 and 13 years old and, the authors concluded that sexual maturation influences neuromotor skills suggesting a possible interaction of factors related to puberty, such as hormone levels for example.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The aim of the present study was to verify the relationship between hormonal markers and biological maturation markers in the neuromotor abilities of female children. Similar to the objective of the present study, Lowe et al, [37] addressed that hormonal markers in the group of estrogens including estradiol interact with strength levels in women throughout life, and Aslam et al, [8] recently reported that there is a relationship between hormone levels during puberty and neuromotor skills in subjects of both sexes. In the same context to the objective of the present study, seeking to find relationships between maturation and neuromotor performance, Volver et al, [27], in a longitudinal study, analyzed 34 female subjects aged between 11 and 13 years old and, the authors concluded that sexual maturation influences neuromotor skills suggesting a possible interaction of factors related to puberty, such as hormone levels for example.…”
Section: Discussionmentioning
confidence: 60%
“…During this process, puberty is a milestone due to the occurrence of faster maturity, mediated by the increase of estrogen group steroid hormones [3][4][5][6]. This group of hormones play an important role in female biological characteristics and may influence the onset of menstrual period and the development of secondary sexual characteristics [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar perspective, Chin et al [38] showed in a previous study that the testosterone levels of male subjects indicate significant relationships with the higher levels of upper limb strength and lean body mass. In this sense, Aslam [39] points out that during puberty there is a peak of hormonal levels such as testosterone, estradiol, and growth hormone, which can significantly influence the morphological structure and the acquisition of muscle strength in young people of both genders.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin signals when there is adequate nutritional intake for the growth spurt, sexual maturation, and menarche (Kaplowitz, 2008 ; Yermachenko & Dvornyk, 2014 ). Ghrelin, or the “hunger hormone” is inversely correlated with the gonadal axis and delays sexual maturation in underfed children with insufficient energy reserves (Aslam, 2020 ). Hence, a delay in the onset of PHV (or tempo) in a skeletal sample may indicate poor nutrition in the individual or adolescent group under study.…”
Section: Skeletal Maturation and The Growth Spurtmentioning
confidence: 99%